The Effect of Method and Ripening Duration on the Content of β-Carotene of Fe’i Banana (Musa troglodytarum L.) - Fredy Leiwakabessy (Hasanuddin University, 2018)
Research was conducted to determine the effect of the method and duration of ripening on the content of β-carotene of Fe’i banana, as well as determine the method and duration of ripening is effective in maintaining the nutritional value of Fe’i Banana. Through laboratory experimental with randomized complete design consisting of 19 groups of treatments and three repetitions, the data obtained were analyzed using statistical tests ANOVA and continued with Duncan test. Results of the analysis showed that method ofripening statistically significant difference (p <0,05) on the content of β-carotene in the banana sticks sky. Long ripening length statistically significant difference (p <0, 05) on the content of β-carotene in the Fe’i Banana. Grilled ripening method is more effective against β-carotene content in the Fe’i Banana and takes1 0 minutes of ripening length more effectively on the content of β-carotene on a Fe’i Banana.